2017
DOI: 10.4103/ijmpo.ijmpo_36_16
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis in acute promyelocytic leukemia: Drug-induced or differentiation syndrome?

Abstract: Acute promyelocytic leukemia (APL) constitutes about 15% of all acute myeloid leukemia patients and can now be treated even without any chemotherapy, with all-trans-retinoic acid (ATRA) and arsenic trioxide (ATO). Acute pancreatitis (AP) is a rare adverse event in APL, which is primarily reported to be secondary to hypertriglyceridemia. Here, we have reported AP developed in a patient of APL, during induction with ATRA and ATO, but it was not associated with hypertriglyceridemia. Rather, it was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In our patient, plenty of APL cells remained when the AP occurred and so she might have been exposed to the inflammatory response associated with differentiation by ATRA. Once the hyperleukocytosis was managed with chemotherapy, ATRA was successfully re‐administered without recurrence of AP; the same as the case of one individual who developed AP without hypertriglyceridemia 3 . When ATRA‐induced AP occurs early during induction therapy with hyperleukocytosis, it would be worth trying re‐administration of ATRA after the hyperleukocytosis is managed with other chemotherapy without ATRA.…”
Section: Patient No Age (Years) Tg (Mg/dl) At Onset Of Ap Onset Of Ap...mentioning
confidence: 98%
See 1 more Smart Citation
“…In our patient, plenty of APL cells remained when the AP occurred and so she might have been exposed to the inflammatory response associated with differentiation by ATRA. Once the hyperleukocytosis was managed with chemotherapy, ATRA was successfully re‐administered without recurrence of AP; the same as the case of one individual who developed AP without hypertriglyceridemia 3 . When ATRA‐induced AP occurs early during induction therapy with hyperleukocytosis, it would be worth trying re‐administration of ATRA after the hyperleukocytosis is managed with other chemotherapy without ATRA.…”
Section: Patient No Age (Years) Tg (Mg/dl) At Onset Of Ap Onset Of Ap...mentioning
confidence: 98%
“…Once the hyperleukocytosis was managed with chemotherapy, ATRA was successfully re-administered without recurrence of AP; the same as the case of one individual who developed AP without hypertriglyceridemia. 3 When ATRA-induced AP occurs early during induction therapy with hyperleukocytosis, it would be worth trying re-administration of ATRA after the hyperleukocytosis is managed with other chemotherapy without ATRA. Written informed consent was obtained from the patient's parents for using her clinical information.…”
mentioning
confidence: 99%
“…All of the patients with hepatic impairment due to the rst exposure to ATO, had their liver function almost normal after the second administration of ATO during consolidation cycles (9). The work of the authors De et al (10) con rms that, in the treatment with ATO, there is a signi cant association between hepatic impairment and an increased leukocyte level. In another study by Chinese authors, the median time to hepatic impairment was 6 days (1-43), and the proposed mechanisms were mitochondrial dysfunction and in ammatory reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Here, we present a typical case of a 55year-old woman with APL who developed WE during treatment for AP after therapy with ATO and ATRA. Some previous cases [4][5][6][7][8][9] have reported that WE is induced by AP and that AP was induced by treatment with ATO and ATRA in patients with APL. However, no reports have described a case of a patient with WE and APL after treatment with ATO and ATRA, or examined whether the administration of ATO and ATRA could induce WE in patients with AP.…”
Section: Introductionmentioning
confidence: 99%
“…Some cases reported that the occurrence of AP was related to the application of arsenic, and some cases were associated with the administration of retinoic acid, which was secondary to hypertriglyceridemia or differentiation syndrome. [4][5][6][7][8][9] Wernicke encephalopathy (WE) is caused by thiamine deficiency and is strongly related to malnutrition, which may result from chronic alcohol abuse, gastrointestinal surgery, prolonged vomiting, or chemotherapy. WE, which is regarded as an acute and severe neuropsychiatric syndrome, is characterised by symptoms of confusion, ophthalmoplegia, and gait ataxia.…”
Section: Introductionmentioning
confidence: 99%